Nonlinear imaging of damage in composite structures using sparse ultrasonic sensor arrays. Issue 5 (19th July 2016) - Ciampa, F.; Pickering, Simon G.; Scarselli, Gennaro; Meo, M.
Summary: In different engineering fields, there is a strong demand for diagnostic methods able to provide detailed information on material defects. Low velocity impact damage can considerably degrade the integrity of structural components and, if not detected, can result in catastrophic failures. This paper presents a nonlinear structural health monitoring imaging method, based on nonlinear elastic wave spectroscopy, for the detection and localisation of nonlinear signatures on a damaged composite structure. The proposed technique relies on the bispectral analysis of ultrasonic waveforms originated by a harmonic excitation and it allows for the evaluation of second order material nonlinearities due to the presence of cracks and delaminations. This nonlinear imaging technique was combined with a radial basis function approach in order to achieve an effective visualisation of the damage over the panel using only a limited number of acquisition points. The robustness of bispectral analysis was experimentally demonstrated on a damaged carbon fibre reinforced plastic (CFRP) composite panel, and the nonlinear source's location was obtained with a high level of accuracy. Unlike other ultrasonic imaging methods for damage detection, this methodology does not require any baseline with the undamaged structure for the evaluation of the defect, nor a priori knowledge of the mechanical properties of the specimen. Copyright © 2016 John Wiley & Sons, Ltd.